Eine Geschichte der Neugier - Stagl, Justin (2002)
My book deals for the first time comprehensively with the techniques (and methodologies) of socio-cultural research in pre-modern societies. Contrary to prevailing opinion, it holds that some form of empirical research in these domains must have been present in all human groups, and every type of society, otherwise they would not have been able to adapt to other groups and to their own Internal changes. I distinguish between three basic research techniques: (1) travel, (2) the survey, and (3) the collection and interpretation of material objects..Chapters I-III follow the development of these techniques from primitive societies via the early civilizations (exemplified by the Ancient near East, Egypt, Israel and the Greco-Roman world) and the Middle Ages to Early Modern Western Society. The mainstay of the book is the period from late humanism to the "scientific revolution" (circa 1570-1660),when all the techniques were refined and two of them (travel and collecting) were methodized. In that period also the age-old barriers against the accumulation of the research results and thus the development of socio-cultural sciences, namely secrecy and topicality, began to break down. I hold that all this contributed decisively to the hegemony of the west over all other World civilizations.Chapters IV-VIII deal with some special problems of the following period from the "scientific revolution" to the onset of Modernity (circa 1660-1800). They are closely interconnected and add some significant and lively details to the generalizations of chapters I-III. Mein Buch behandelt zum erstenmal zusammenfassend die Techniken (und Methodologien) der Sozial- und Kulturforschung vormoderner gesellschaften. Im Unterschied zur vorherrschenden meinung geht es davon aus, dass es irgendeine Form empirischer Forschung auf diesen gebieten in allen menschlichen Gruppen und Gesellschaftsformen gegeben haben muss, da diese sich ansonsten nicht an andere gruppen sowie an die eigenen inneren Wandlungen hätten anpassen können. Ich unterscheide drei grundlegende Forschungstechniken: (1 ) das reisen, (2) die Umfrage und (3) das Sammeln und Interpretieren konkreter Objekte.Kapitel I-III folgen der Entwicklung dieser Techniken von den archaischen Gesellschaften über die frühen Hochkulturen (exemplifiziert durch den Alten Orient, Ägypten, Israel und die griechisch-römische Welt) und das Mittelalter bis zum Europa der Frühen Neuzeit. Das Zentrum des Buches bild ...